Features of Applying Biological Preparations in the Technology of Potato Growing on Gray Forest Soils - D.V, Vinogradov; O.N, Terekhina; N.V, Byshov; M.M4., Kryuchkov; N.I, Morozova; O.A, Zakharova (International Journal of Engineering and Technology, 2018)
The article offers an analysis of investigating some experimental potato plantations. Potato is a widespread agricultural crop, which is one of the main food and industrial crops in Russia. The complex conditions of the modern period necessitate the development of new technologies adapted to the modern conditions of land use. One of the most important problems of potato growing is the lack of knowledge of agro biological properties of modern cultivars and their response to the biological methods of potato growing. Identifying the most effective of them and the best ways to use them is an actual problem of modern agriculture.The results of field experiments indicate that biological preparations (Albite and Biocomposite-Correct) have a multifunctional effect on potato plants. As a result of these studies, some positive data were obtained which showed the effect of the preparations on the onset of potato development phases and on the yield increase of potato test varieties. The maximum yield increase was formed during complex treatment of Gala cultivar potatoes with Biocomposite-Correct and was 2.52 t/ha as compared with the control variant, and the highest yield increase of Ryabinushka cultivar was achieved with the complex treatment with Albite and amounted to 2.12 t/ha.Â Â